Reconstruction of the Mediation Model in the Resolution of Customary Law Disputes as an Effort to Integrate it into the National Legal System - Umar Hasan; Sasmiar Sasmiar; Suhermi Suhermi; Windarto Windarto; Rifqi Pratama Putra (JURNAL AKTA, 2026)
The diversity of customary law in Indonesia reflects the reality of legal pluralism that exists within society. However, the existence of customary mediation mechanisms as a means of dispute resolution is often overlooked in the national legal system, which is oriented towards formal legality. This shows the imbalance between living law and positive law. This study uses a normative juridical method with a conceptual, legislative, and case-based approach to examine the position of customary mediation law in the national legal system and to formulate an ideal model of customary mediation that can be accommodated legally and harmoniously. The results of the study show that philosophically and constitutionally, customary law has strong legitimacy as recognized in Article 18B paragraph (2) of the 1945 Constitution and Article 2 of the 2023 Criminal Code concerning living law in society. Empirically, customary mediation models in various regions such as Aceh and Kalimantan are capable of delivering restorative, participatory, and humanistic justice, despite facing the challenges of modernization and the principle of legality. Therefore, the integration of customary mediation into the national legal system needs to be realized through the strengthening of customary institutions and normative regulations that guarantee equal rights and legal certainty. Customary mediation should ideally become a model of restorative justice unique to Indonesia, rooted in cultural values and the principle of deliberation to reach consensus.